Investors Selection Among Three Different Companies: TESLA, BAIDU and LEA - Cui, Xuanyi (Transactions on Economics, Business and Management Research, 2024)
The research mainly focusses on different investors’ choices of TESLA, BIDU and LEA. In the era of economic globalization and digitalization, investment has become an important way of financial growth for individuals and enterprises. Understanding the value and importance of investments can help people make more informed financial decisions, achieve asset appreciation and manage risk. This research collects data on risk, profitability and market ratio. Debt Ratio, Beta and Market Value are analysed in the Risk part, Total Assets Turnover, Profit Margin, ROA and ROE are analysed in the Profit part, P/E Ratio, P/B Ratio, Dividend Yield, PEG Ratio, Index, Current Stock Price and 200 day moving average. According to these data, the research finds that Index investors, Growth investors and Momentum investors will choose TESLA, PEG investors and Index investors will choose BIDU, PEG investors and Momentum investors will choose LEA. The results of the research help different kinds of investors to choose companies to invest in.